Indikator Capaian Keberhasilan Program PLPBK Untuk Peningkatan Kualitas Lingkungan Permukiman - Susi Diahlita Sari .; Alfitri .; M.Yazid . (Universitas Khairun, 2015)
This research was aimed to assess the quality of environmental which islocated in priority program planning of PLPBK. This research was conductedon December 2014 on location RT 02, RT 05 and RT 31 Kelurahan Piparejaas direct beneficiaries of the activities PLPBK program of 2013. This researchincluding comparing the level of achievement of a target of the PLPBKprogram by counting the level of community satisfaction with the indicators ofincreased access community in neighborhood, increased convenience inneighborhood, and increased quality of infrastructure in neighborhood. Fromthe distributed questionnaire, the measurement of opinion about socialphenomena that evolve by using a Likert scale with the standard ofcommunity's satisfaction level neighborhood, and then the data ofrespondents was tested with validity test and reliability test.From the analysis quality of neighborhood is obtained results 85.97% whichthis results exceeded the target set by the PLPBK program ie more than 80%of community in priority areas said they were satisfied and achieve very goodcategory. It can be concluded based on the analysis quality of theneighborhood and analysis of the costs benefit from the program PLPBK inpriority areas of Kelurahan Pipareja Kecamatan Kemuning effective in theimplementation of the program structuring neighborhood. Suggestions in thisresearch are expected to community and relevant government for the futurebe able to collaborate in improving quality of neighborhood in urban areas, sothat urban areas are becoming viable as a place to stay to live.